GAME SCORING NON PLAYER CHARACTER MENGGUNAKAN AGEN CERDAS BERBASIS FUZZY MAMDANI - Astrid Novita Putri; Mochamad Hariadi; Ruri Suko Basuki (Jurnal Teknologi Informasi - Cyberku (JTIC), 2019)
Game are activity most structure, one that ordinary is done in fun and also education tool and help todevelop practical skill, as training, education, simulation or psychological. On its developing currentGame have until 3D. In one Game, include in First Person Shutter necessary scoring one that intent tomotivate that player is more terpacu to solve Game until all through, on scoring Super Mario's GameBoss, Compass does count scoring haven't utilized Artifical Intelligent so so chanted, while player meetwith enemy (Non Player Character) really guns directly dead, so is so easy win. Therefore at needs acount scoring interesting so more terpacu in menyelasaikan problem Scoring accounting point for FirstPerson Shutter's Game .This modelling as interesting daring in one Game, since model scoring one thateffective gets to motivate that player is more terpacu in plays and keep player for back plays. Besidesmodel scoring can assign value that bound up with Game zoom.On Research hits scoring this Game willmake scoring bases some criterion which is health Point, Attack point, Defending point, And Dammagewhat do at miiliki zombie,then in this research do compare two method are methodic statistic and Fuzzy.Result of this research 90 % on testing's examination and on eventually gets to be concluded that fuzzy'smethod in trouble finish time more long time but will player more challenging to railroad